The Effect of Training Methods and Hand Eye Coordination on the Accuracy of Backhand Drive in Table Tennis Athletes - A Fani Kamalussadad; Harry Pramono; Endang Sri Hanani (JUARA : Jurnal Olahraga, 2022)
This study aimed to analyse the effect of the two-way and random feed drill training method on the accuracy of the backhand drive of PTM barokah Jaya Purwokerto, table tennis athletes. This study used an experimental method with a 2x2 factorial design and data analysis techniques using Analysis Of Variance (ANOVA) at the significance level (α: 0.05). The population in this study were PTM Barokah Jaya Purwokerto table tennis athletes, totalling 28 people. The results of this study: There are differences in the effect of the random feed and two-way drill training methods on the backhand drive. Two-way bait drill exercise is better than unexpected bait drill on the accuracy of backhand drive PTM Barokah Jaya Purwokerto table tennis athletes. There are differences in the effect of high and low hand-eye coordination on the accuracy of the backhand drive. Athletes with high hand-eye coordination are better than athletes with low hand-eye coordination against PTM Barokah Jaya Purwokerto table tennis athletes. There was no interaction between training methods and hand-eye coordination on the accuracy of backhand drives in PTM Barokah Jaya Purwokerto athletes. The conclusions of this study are 1). The two-way feed drill training method is better than the random feed drill. 2). Players with high hand-eye coordination are better than those with low hand-eye coordination. 3). there was no interaction between training methods and eye-hand coordination on the accuracy of the backhand drive of PTM Barokah Jaya Purwokerto table tennis athletes.